Analisis Potensi Lestari Hasil Tangkapan Trammel Net Di Kabupaten Indramayu - Dedi Supriadi; Bangun Ichsanudin; Aman Saputra; Restu Widayaka (Fakultas Perikanan dan Ilmu Kelautan Universitas 17 Agustus 1945 Cirebon, 2021)
This study aims to analyze the Catch Per Unit Effort (CPUE) and Maximum Sustainable Yield (MSY) from the catch of trammel net fishing gear by fishermen in Indramayu Regency, West Java. The research method used is descriptive method, which is a method to create a systematic, factual and accurate description of the facts, characteristics and relationships of environmental factors or phenomena being studied. Data analysis was carried out on the catch and catch effort in the last 5 years (2011-2015) on trammel net fishing gear. Trammel net fishing gear is environmentally friendly fishing gear and is an effective fishing tool in fishing productivity with the composition of the catch consisting of the main catch is tiger shrimp (Penaeus monodon) and bycatch such as tigawaja fish (Johnius belangeri), petek Leiognathus bindus) and layur (Trichyurus haumela). The highest annual productivity of trammel net fishing gear during 2011-2015 occurred in 2011 and 2014 at 0.018 tons / trip and the lowest productivity occurred in 2015 at 0.013 tons / trip, and the maximum sustainable catch or MSY in Indramayu Regency was 32147, 1 ton / year, with an estimated optimum fishing effort of 103516.67 trips for one year and R2 of 0.2977. This study aims to analyze the Catch Per Unit Effort (CPUE) and Maximum Sustainable Yield (MSY) from the catch of trammel net fishing gear by fishermen in Indramayu Regency, West Java. The research method used is descriptive method, which is a method to create a systematic, factual and accurate description of the facts, characteristics and relationships of environmental factors or phenomena being studied. Data analysis was carried out on the catch and catch effort in the last 5 years (2011-2015) on trammel net fishing gear. Trammel net fishing gear is environmentally friendly fishing gear and is an effective fishing tool in fishing productivity with the composition of the catch consisting of the main catch is tiger shrimp (Penaeus monodon) and bycatch such as tigawaja fish (Johnius belangeri), petek Leiognathus bindus) and layur (Trichyurus haumela). The highest annual productivity of trammel net fishing gear during 2011-2015 occurred in 2011 and 2014 at 0.018 tons / trip and the lowest productivity occurred in 2015 at 0.013 tons / trip, and the maximum sustainable catch or MSY in Indramayu Regency was 32147, 1 ton / year, with an estimated optimum fishing effort of 103516.67 trips for one year and R2 of 0.2977.